Pembuktian Unsur Rencana dalam Perkara Honor Killing: Deliberasi Keluarga dan Skema Persiapan - Zul Khaidir Kadir (Jurnal Intelek Insan Cendikia, 2026)
Honor killing is frequently framed in judicial proceedings as an act triggered by an immediate emotional outburst, leading to a narrowed or weakened assessment of premeditation. Such framing risks misclassification, as decision-making in honor killings often unfolds through brief yet deliberative chains of choice and may be distributed among multiple family members. This article aims to formulate honor-killing-specific indicators for proving premeditation by focusing on family deliberation and preparation schemes that remain verifiable through criminal evidence.The study employs normative legal research with a doctrinal and argumentative orientation, using statutory, conceptual, and systematic approaches. Analysis draws on provisions governing premeditated murder and principles of criminal evidence to connect the element of planning with observable conduct rather than subjective admissions. The findings demonstrate that the distinction between emotional outburst and premeditation should rest on the structure of decision-making rather than emotional intensity. Family deliberation operates as an internal authorization mechanism that enables role assignment and directs preparatory actions. Preparation schemes may be identified through weapon procurement, victim luring, surveillance, timing and location selection, and post-offence coordination, provided these acts maintain a logical connection with pre-offence preparation. These indicators are organized into a premeditation checklist based on evidentiary convergence across decision, preparation, and post-offence clusters. The checklist functions as a judicial reasoning aid that enables systematic scrutiny of spontaneity claims while preserving the foundational principles of criminal proof.